"Near-to-Zero-Energy Floor" in a Campus Building from 1971. (November 2015) - Tywoniak, Jan; Sojková, Kateřina
Abstract: In 2013, a campus building in Prague, built more than 40 years ago, was partially refurbished. Its old curtain wall with very poor performance was completely removed and replaced by a new element façade of significantly higher quality, which meets today's recommendations concerning the energy efficiency. The comfort requirement was satisfied partially – the effect of overheating was almost entirely eliminated without the need of mechanical cooling. It was still necessary to improve the quality of ventilation. Therefore, a study on the possibility and effects of installing an additional ventilation system was conducted. As a pilot project, a complex solution of one selected floor was implemented. This solution is described and commented upon in this paper.